Towards a dialect-neutral assessment instrument for the language skills of Afrikaans-speaking children: the role of socioeconomic status*. Issue 2 (23rd February 2012) - SOUTHWOOD, FRENETTE
ABSTRACT: The aims of the study were to establish whether there is a correlation between the socioeconomic background of Afrikaans-speaking children and their performance on a dialect-neutral language test, and to ascertain whether the allowance the test currently makes for parental education level is sufficient. The Afrikaans version of the Diagnostic Evaluation of Language Variation (Seymour, Roeper & de Villiers, 2005 a ) was administered to 231 Afrikaans-speaking children age 4 ; 0 to 9 ; 11 from various socioeconomic backgrounds. A positive correlation was found between the composite language scores as well as the scores for each of the language domains (syntax, pragmatics, semantics) and the primary female caregivers' highest level of education. Children with father figures present did not outperform those without. It appears that the original manner of accommodating parental education level in interpreting the children's language scores on the test is sufficient and need not be refined for the South African context.